Deletion of the forebrain mineralocorticoid receptor impairs social discrimination and decision-making in male, but not in female mice - Ter Horst, Judith P.; van der Mark, Maaike; Kentrop, Jiska; Arp, Marit; van der Veen, Rixt; De Kloet, Ronald; Oitzl, Melly S. (Frontiers in Behavioral Neuroscience, 2014)
Social interaction with unknown individuals requires fast processing of information to decide whether it is friend or foe. This process of discrimination and decision-making is stressful and triggers secretion of corticosterone activating mineralocorticoid receptors (MR) and glucocorticoid receptors (GR). The MR is involved in appraisal of novel experiences and risk assessment. Recently, we have demonstrated in a dual-solution memory task that MR plays a role in the early stage of information processing and decision-making. Here we examined social approach and social discrimination in male and female mice lacking MR from hippocampal-amygdala-prefrontal circuitry and controls. The social approach task allows the assessment of time spent with an unfamiliar mouse and the ability to discriminate between familiar and unfamiliar conspecifics. The male and female test mice were both more interested in the social than the non-social experience and deletion of their limbic MR increased the time spent with an unfamiliar mouse. Unlike controls, the male MRCaMKCre mice were not able to discriminate between an unfamiliar and the familiar mouse. However, the female MR mutant had retained the discriminative ability between unfamiliar and familiar mice. Administration of the MR antagonist RU28318 to male mice supported the role of the MR in the discrimination between an unfamiliar mouse and a non-social stimulus. No effect was found with a GR antagonist. Our findings suggest that MR is involved in sociability and social discrimination in a sex-specific manner through inhibitory control exerted putatively via limbic-hippocampal efferents. The ability to discriminate between familiar and unfamiliar conspecifics is of uttermost importance for territorial defense and depends on a role of MR in decision-making.